Die Neue Welt in der Perspektive Alexander von Humboldts - Pfeifer, Gottfried (ERDKUNDE, 1959)
Alexander von Humboldt's importance as natural scientist has been much appreciated on occasion of the centenary of his death. The present paper is to point out Alexander von Humboldt's excellence as human geographer. His comprehensive work on his travels, especially in the books on Mexico and Cuba, gives a detailed analysis of the cultural, social, economic, and geographical situation of the New World of his time. In literature we find but scarce hints that a similar analysis deals with Venezuela, too. Caracas, Habana, and Mexico are the bases for Alexander von Humboldt's description of the New World in the problematic transition period from colonial status with economic dependence to emancipation and abolition of slavery. He finally reviews the results of his own travels comparing them with the material collected from the literature on Brazil and the United States.